An equity analysis of utilization of health services in Afghanistan using a national household survey - Christine Kim; Khwaja Mir Ahad Saeed; Ahmad Shah Salehi; Wu Zeng (BMC, 2016)
Abstract Background Afghanistan has made great strides in the coverage of health services across the country but coverage of key indicators remains low nationally and whether the poorest households are accessing these services is not well understood. Methods We analyzed the Afghanistan Mortality Survey 2010 on utilization of inpatient and outpatient care, institutional delivery and antenatal care by wealth quintiles. Concentration indexes (CIs) were generated to measure the inequality of using the four services. Additional analyses were conducted to examine factors that explain the health inequalities (e.g. age, gender, education and residence). Results Among households reporting utilization of health services, public health facilities were used more often for inpatient care, while they were used less for outpatient care. Overall, the utilization of inpatient and outpatient care, and antenatal care was equally distributed among income groups, with CIs of 0.04, 0.03 and 0.08, respectively. However, the poor used more public facilities while the wealthy used more private facilities. There was a substantial inequality in the use of institutional delivery services, with a CI of 0.31. Poorer women had a lower rate of institutional deliveries overall, in both public and private facilities, compared to the wealthy. Location was an important factor in explaining the inequality in the use of health services. Conclusions The large gap between the rich and poor in access to and utilization of key maternal services, such as institutional delivery, may be a central factor to the high rates of maternal mortality and morbidity and impedes efforts to make progress toward universal health coverage. While poorer households use public health services more often, the use of public facilities for outpatient visits remains half that of private facilities. Pro-poor targeting as well as a better understanding of the private sector's role in increasing equitable coverage of maternal health services is needed. Equity-oriented approaches in health should be prioritized to promote more inclusive health system reforms.